Phosphorus magnetic resonance spectroscopy in malformations of cortical development - Celi Santos Andrade (Arquivos de Neuro-Psiquiatria)
IntroductionMalformations of cortical development (MCD) result from disruptions in the dynamic process of cerebral corticogenesis and are important causes of epilepsy, motor deficits and cognitive impairment.ObjectivesThe aim of this study was to evaluate phospholipids metabolism in vivo in a series of patients with epilepsy and MCD.MethodsThirty-seven patients with MCD and 31 control subjects were studied using three-dimensional phosphorus magnetic resonance spectroscopy (31P-MRS) at a 3.0 T scanner. Quantification methods were applied to the following resonances: phosphoethanolamine (PE), phosphocholine (PC), glycerophosphoethanolamine (GPE), glycerophosphocholine (GPC), inorganic phosphate (Pi), phosphocreatine (PCr), and a-, b-, and g-adenosine triphosphate (ATP). The magnesium (Mg2+) levels and pH were calculated based on PCr, Pi and b-ATP chemical shifts.ResultsCompared to controls, the MCD lesions exhibited lower pH values and higher Mg2+ levels (p<0.05). The lesions also presented significant reduction of GPC and PDE, and an increased PME/PDE ratio. The otherwise normal appearing parenchyma also demonstrated lower pH values in the frontoparietal cortex and bilateral centrum semiovale.ConclusionsOur data support the idea that metabolic impairments occur in the lesions of MCD, with propagation to remote normal appearing parenchyma. The results also suggest that there are membrane turnover disturbances in MCD lesions.